Impact of Blood Pressure in the Early 40s on Left Atrial Volumes in the Mid‐60s: Data From the ACE 1950 Study - Rønningen, Peter Selmer; Berge, Trygve; Solberg, Magnar Gangås; Enger, Steve; Pervez, Mohammad Osman; Orstad, Eivind Bjørkan; Kvisvik, Brede; Aagaard, Erika Nerdrum; Lyngbakken, Magnus Nakrem; Ariansen, Inger; Røsjø, Helge; Steine, Kjetil; et al. (Journal of the American Heart Association, 2022)
Background Echocardiographic measures of left atrial volumes are powerful predictors of cardiovascular events and important for assessing diastolic dysfunction. Despite this, there is limited knowledge of factors influencing left atrial remodeling. In particular, the impact of blood pressure in those in their early 40s on left atrial volumes later in life has not been sufficiently elucidated. Methods and Results We linked data from individuals born in 1950 who participated in the Age 40 Program, and the ACE (Akershus Cardiac Examination) 1950 Study. We divided the study population into quartiles of systolic blood pressure in their early 40s and assessed the proportion of individuals with an enlarged left atrium in their mid-60s. The associations between blood pressure and left atrial volumes were assessed in linear regression analyses. Of the 2591 individuals included in this study, 1302 (50.3%) were women, and the mean age in the Age 40 Program was 40.1±0.3 years. Systolic blood pressure was 128.1±13.6 mm Hg and diastolic blood pressure was 78.3±9.5 mm Hg. Mean age in the ACE 1950 Study was 64.0±0.6 years. The proportion of individuals with an enlarged left atrium increased across the quartiles of systolic blood pressure ( =0.001). Systolic blood pressure was independently associated with left atrial volumes; the end-systolic volume was 0.09 mL (95% CI, 0.04-0.14 mL) larger per 1-mm Hg higher systolic blood pressure. Conclusions Our findings suggest that increased blood pressure in those in their early 40s is relevant for left atrial remodeling later in life. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT01555411.